NFC-based data retrieval device - Abd Wahab, Mohd Helmy; Mohamed Suhaimi, Nur Farezan; Mohamad Mohsin, Mohamad Farhan; Mustapha, Aida; Samsudin, Noor Azah; Ambar, Radzi (IOP Publishing, 2018)
This paper describes the design and development of data retrieval system using near field communication (NFC) protocol to read and transfer data from the device storage panel located at the recycle bin. In existing systems, data are manually collected from the storage device using the SD card and sent for upload to regional workstation of the data center, which is located at the central server. The device automatically establishes the NFC connection with the recycle bin panel and once the connection is established, data will automatically be transferred to the device and the current data storage in the recycle bin will be erased. Next, the collected data will be uploaded to the server through regional workstation